Analysis for Science Librarians of the 2017 Nobel Prize in Chemistry: Cryo-electron Microscopy. Issue 1 (2nd January 2018) - Wrublewski, Donna T.
ABSTRACT: The 2017 Nobel Prize in Chemistry recognized three scientists for their contributions to developing the technique of cryo-electron microscopy (cryo-EM) for the imaging and structure elucidation of biomolecules. Richard Henderson's dogged pursuit led to the first Ångstrom-level visualization of a biomacromolecule. Joachim Frank developed computational imaging techniques to produce 3D visualizations from collections of low-contrast EM images. Jacques Dubochet was the first to use vitrified, noncrystalline water as a medium for cryo-EM of biological specimens. Each of these scientists has contributed a key technique or insight into using cryo-EM to visualize biological particles that heretofore had been elusive to visualization. Recent improvements in electron detector technology have helped realize the fuller potential of cryo-EM.